Ultrasound, computed tomography and surgical observations in the evaluation and staging of the renal cell carcinoma - Mohson, Khaleel I.; Ali, Hana A. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: The evaluation and staging of renal cell carcinoma (RCC) has dramatically changed with the introduction of cross-sectional imaging. Nowadays, small renal lesions are easily detected by computed tomography (CT) examination while missed by other modalities.Objective: To determine whether ultrasound (US) or CT scan is the optimum imaging modality for the evaluation of the renal masses.Patients and methods: This is a comparative study in which 30 patients with hematuria were attending the urological consulting clinic in Ghazzi Al-Harriry hospital, Baghdad, Iraq from May 2016 to July 2017 were subjected to abdominal US and CT scan.Results: The patients included in the study were 19 females and 11 males. The results of US, unenhanced and contrast CT for characterization of the consistency of renal mass were 63.4%,56.7%, and 60% respectively for the solid, while the cystic were 23.3%,23.3%, and 26.6% and for complex was 13.3%,20% and 13.4% respectively. The size of the masses was compatible in 60% of cases. Mass surface regularity was compatible in 93.4%.Regarding mass position, the US showed that 96.7% to be confined to the kidney and 4.3% extended outside, while 66.6% were judged to be confined by CT scan, which is nearly similar to the operative findings which revealed 60% localized masses to kidney and 40% extending outside the kidney.Conclusion: the US is a good modality to start with in the assessment of renal lesions, but CT scan is still the main tool to diagnose and stage RCC.